Blaming, Resisting, and Reframing Authority: A Pragmatic Critical Discourse Analysis of Instagram Narratives during Flood Disasters in Sumatra - Herlin Triana; Vivi Indriyani; Amelia Yuli Astuti; Ratih Purwasih (Master Program in Linguistics, Diponegoro University, 2026)
Public discourse on social media has given rise to various narratives that often spark debate and influence public perceptions of information. This study aims to examine pragmatic patterns and discursive constructions in social media narratives related to disaster events, with a focus on how users construct, challenge, and reframe authority. This study employs an interpretive qualitative approach using Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA), which encompasses text analysis, discursive practices, and social practices. Data in the form of Instagram posts were analyzed step-by-step through the identification of linguistic elements, patterns of discourse production and distribution, and their connection to the broader social context. A pragmatic approach was used to identify speech acts, implicatures, and attitude constructions in digital discourse. The research findings indicate that disaster discourse is constructed through evaluative lexical strategies, irony, metaphors, and visual reinforcement that represent ecological crises and social inequalities. Audience responses exhibit dominant patterns of blaming, resisting, and reframing, which consistently appear in comments, likes, and content shares. These findings confirm that social media functions as a discursive arena that not only represents the reality of disasters but also shapes collective criticism of policies, power, and environmental management.